EDUKASI GENERASI MUDA SIAP VAKSINASI COVID-19 - Ilil Maidatuz Zulfa; Fitria Dewi Yunitasari (Jurnal Abdi Masyarakat Kita, 2021)
Vaccination program for Covid-19 in Indonesia has been conducted since 13th of January 2021. However, the vaccination process has been accompanied by an increase false information that can lead to the decrease of public acceptance. Therefore, public education strengthening is a key concerns to succed the vaccination program. This was a report of public education strengthening activity conducted in April 2021 aimed to increase public awareness about Covid-19 vaccination program. There were 34 highschool students joined in the event. The result showed after joining the events 14,7% of students who refuse to support vaccinated program claim thet they are ready for vaccination. In conclusion, continuity in public education strengthening is essential to increase public acceptance about Covid-19 vaccination.